Effect of the granular gradient of plastic waste added on the properties of hot asphalt mixtures (Damascus University Journal for engineering sciences, 2025)
Plastic waste is widely spread all over the world as a result of the increasing spread of the plastic industry, which results in waste in huge quantities andthus a major environmental, economic and health problem. Recycling and reusing this waste as additives in engineering projects, especially road projects (flexible paving) is one of the positive solutions to get rid of these wastes instead of land filling or burning and other other methods, especially if this is reflected positively on the properties of asphalt mixtures. In this scientific article, we discussed the idea of ​​adding plastic waste to asphalt mixtures by using High Density Polyethylene (HDPE) as an example of this waste, with a focus on the softness of plastic waste and the extent of its impact on the properties of the asphalt mixture. Most of the reference research in this field indicated that Grinding plastic waste with dimensions sometimes up to 3mm and sometimes 2.36mm and it can be 600µ. In our research, two different grades of HDPE were studied. The first gradation: (HDPE) with a size ranging from 4.75-0.425 mm). We will consider it a  first gradient in this paper The second gradation: (HDPE) with a size ranging from 0.075-1) mm) and it will be a second gradient in the research HDPE was added to both grades in percentages (0.4%-0.6%0.8%1%) of the weight of the used aggregates. We adopted the experimental method in the research, through which we concluded that the addition of polymer, both the first and second gradients, has significantly increased stability compared to the reference mixture, , but the second (HDPE) gradient has given better results for the properties of the mixture (stability, air voids, as well as density) at the ratio The addition of 0.8% of the weight of the gravel (stability increased 27%) density and air voids decreased  lowly. Therefore, second grading is generally considered a better application for such.
Keywords: : plastic waste; hot asphalt mixtures; road paving